Effects of γ-butyrobetaine and l-carnitine on carnitine concentrations in various muscle tissues of finishing pigs - Benz, J.M.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
The primary method of L-carnitine production, similar to the biological process that occurs in the liver and kidneys, is from microbial fermentation of γ-Butyrobetaine. Therefore, the objective of this study was to see if supplementing the diet with γ-Butyrobetaine would increase organ and muscle tissue carnitine concentrations. One-hundred-twenty-five barrows were fed diets containing either L-carnitine (100 ppm), γ-Butyrobetaine (100 ppm) or a combination of L-carnitine (50 ppm) and γ-Butyrobetaine (50 ppm). The addition of L-carnitine, γ-Butyrobetaine and the combination of L-carnitine and γ-Butyrobetaine increased (P<0.01) free carnitine concentration in the longissimus, diaphragm, and heart. L-carnitine and the combination of L-carnitine and γ-Butyrobetaine increased (P<0.01) free carnitine concentration in the kidney. Therefore, these results suggest that γ-Butyrobetaine and/or L-carnitine can be used to increase carnitine concentrations of organ and muscle tissues.
Keywords: Swine; Vitamins; L-carnitine; γ-Butyrobetaine